Autologous stem cell transplantation in a case of treatment resistant central nervous system lupus - Trysberg, E (2000)
This case report describes a young woman with systemic lupus erythematosus starting at 16 years of age and giving rise to severe neurological complications including bilateral opticus neuritis and transverse myelitis. Despite heavy immunosuppression her condition steadily aggravated. At this point it was decided to perform autologous stem cell transplantation. Haematopoietic stem cells were mobilised with cyclophosphamide and granulocyte colony stimulating factor. Enrichment of CD34(+)cells was followed by depletion of peripheral T and B cells. The post-transplantation course was uneventful, and all the neurological deficits improved promptly during the 15 months of follow up. This is the first description of successful autologous stem cell transplantation in a case of life threatening central nervous system lupus.